2010
DOI: 10.1055/s-0030-1267180
|View full text |Cite
|
Sign up to set email alerts
|

Interval and Strength Training in CAD Patients

Abstract: This study sought to study the effect of high intensity aerobic interval endurance training on peak stroke volume and maximal strength training on mechanical efficiency in coronary artery disease (CAD) patients. 8 CAD patients (age 61.4 ± 3.7 years) trained 30 interval training sessions with 4 × 4 min intervals at 85-95% of peak heart rate while 10 CAD patients (age 66.5 ± 5.5 years) trained 24 sessions of maximal horizontal leg press. In the interval training group peak stroke volume increased significantly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 28 publications
(37 reference statements)
4
29
1
1
Order By: Relevance
“…An improvement in work capacity is therefore typically associated with an increased wellbeing in everyday life, since it reduces the relative intensity on the daily tasks [10, 33, 34]. The improvement in VO 2max⁡ observed in our study is similar to what have previously been reported following a whole body high intensity (>85% of HR max⁡ ) training intervention in a wide range of patient groups [710, 35, 36], as well as and in healthy subjects [21, 37] and old subjects [37]. The magnitude of VO 2max⁡ improvement may be influenced by training status, age, or pathology [710].…”
Section: Discussionsupporting
confidence: 86%
“…An improvement in work capacity is therefore typically associated with an increased wellbeing in everyday life, since it reduces the relative intensity on the daily tasks [10, 33, 34]. The improvement in VO 2max⁡ observed in our study is similar to what have previously been reported following a whole body high intensity (>85% of HR max⁡ ) training intervention in a wide range of patient groups [710, 35, 36], as well as and in healthy subjects [21, 37] and old subjects [37]. The magnitude of VO 2max⁡ improvement may be influenced by training status, age, or pathology [710].…”
Section: Discussionsupporting
confidence: 86%
“…Thus, as exercise intensity has been well documented as a crucial stimulus to maintain and improve VO 2max in young subjects , it is highly likely that the reduction in exercise intensity may have a major impact also on VO 2max in the old. Additionally, although similar percentage improvements of 10-30 % in VO 2max have been commonly documented following effective aerobic endurance training interventions in both young and old subjects, conclusions about exercise-induced metabolic plasticity have been clouded by differences in initial aerobic fitness Helgerud et al 2011;Osteras et al 2005;Slordahl et al 2005;Wisloff et al 2007). Adaptations to both central and peripheral components of the oxygen transport system contribute to changes in VO 2max , with increases in Q max , achieved by an enhanced SV, suggested to be important in augmenting whole body exercise capacity Helgerud et al 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Additionally, although similar percentage improvements of 10-30 % in VO 2max have been commonly documented following effective aerobic endurance training interventions in both young and old subjects, conclusions about exercise-induced metabolic plasticity have been clouded by differences in initial aerobic fitness Helgerud et al 2011;Osteras et al 2005;Slordahl et al 2005;Wisloff et al 2007). Adaptations to both central and peripheral components of the oxygen transport system contribute to changes in VO 2max , with increases in Q max , achieved by an enhanced SV, suggested to be important in augmenting whole body exercise capacity Helgerud et al 2011). However, it is currently unknown how VO 2max , Q max , and SV max in old and young subjects with equal initial exercise capacity respond to the same high aerobic intensity whole body exercise training.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These individuals should increase their training load very carefully over a long period of time and should be educated concerning load regulation with special diligence. Under certain premises, in some patient groups, the use of high intensity training (HIT) is considered effective and safe (Guiraud et al, 2012;Helgerud et al, 2011). Preliminary studies showed that during or immediately after a total of 46,000 h of supervised intensive interval exercise, two non-lethal cardiac events (cardiac arrests) occurred, and one event occurred during 129,000 h of moderate intensity training (Rognmo et al, 2012).…”
Section: Side Effects and Potential Of Self-regulated Exercise Trainimentioning
confidence: 99%